TRILOGI KEPEMIMPINAN KI HADJAR DEWANTARA - Bagus Dwi Widyantoro; Djumadi Purwoatmodjo; Tasliyatun Ni'mah; Slamet Utomo; Ahmad Hariyadi (Equity In Education Journal, 2023)
This conceptual article aims to examine Ki Hadjar Dewantara's Leadership Trilogy at the education unit level, especially in elementary schools, which still experience many problems and obstacles, reflected in the various conflicts that occur between school principals and teachers, and school members. Principals at the elementary school unit level in carrying out their duties to lead the agenda for improving employee (teacher) discipline only refer to the level of attendance and achievement, without paying attention to the difficulties experienced by teachers in achieving the targets that have been given. Therefore, the concept of Ki Hadjar Dewantara's Leadership Trilogy is one of the fundamental answers to overcoming various existing problems and creating a conducive climate in elementary schools; This is because the concepts of "Tut Wuri Handayani" (behind giving guidance) and "Ing Madyo Mangun Karso" (in the middle giving encouragement) will not run optimally without "Ing Ngarso Sung Tulodho", namely the leader (pamong) who acts as an example to its members. Setting an example, ngemong, is not only seen from ability but also ethically and morally.